Proces pilota Francisa Garry’ego Powersa z 17-19 sierpnia 1960 roku w propagandzie sowieckiej - Kisztelińska, Agnieszka (Acta Universitatis Lodziensis. Folia Historica, 2002)
At 5:36 a.m. Moscow time on May 1st, I960, an unknown plane violated the stale frontier of the USSR at point 20 km south-east of the town Kirovabad, the Tajik Soviet Socialist Republic, intruded into the airspace of the Union of Soviet Socialist Republics. The plane which violated the Soviet Frontier was tracked continuously by units of the Soviet anti-aircraft defence. The examination of the plane’s wreckage and special equipment it carried established that it was an American plane of the „Lockheed U-2” type, designed for (lights al great altitudes, adapted for intelligence purposes and, to this end, equipped for aerial photography and radio reconnaissance from great heights. Besides the plane, the main evidence of real destination of the flights was pilot – Francis Garry Powers who saved and took part in the trial in Moscow in August 1960. The main purpose of this article is to show how Soviet leaders used propaganda methods in order to gain political aims. This paper is based on documents published as a The trial of the U-2, Exclusive Authorized Account of the Court Proceedings of the Case of Francis Garry Powers, Heard before the Military Division of the Supreme Court of the U.S.S.R. Moscow August 17, 18, 19, 1960 and American and Polish documents connected with this case.